Beyond Otaku Community to Global Business: Manga in Academia—a Literature Review - Phornprapha, Jiraporn; Podsatiangool , Weerayuth (Thai Journal of East Asian Studies, 2019)
Comics is commonly appreciated for its entertaining value but ignored for other values due to its lack of seriousness. Japanese comics is in no way an exception. Despite its popularity in the global market, manga is the reading material that is far from being intellectual. However, the study on manga suggested differently. Manga is treated with seriousness in academia. This article reviewed how manga was studied in various aspects. It was found that manga was studied from multidisciplinary, mainly from cultural studies. Other studies of manga focus on the translation of manga, its role in education and media, and its application as soft power and cultural commodities. While manga is interrelated to merchandise from entertainment industry and other consumer products even in automobile industry, its value in economy is less explored. Porter (1990) indicated that innovation was crucial for a business to remain competitive. Therefore, this article suggested that to understand the value of manga in economy, innovation studies should be taken into account in the future research of manga studies.